RANCANG BANGUN SISTEM INFORMASI PERSEDIAAN STOK BARANG BERBASIS WEBSITE (STUDI KASUS: PT. PERDANA SAKTI INDONESIA) - Sannia Putri Ariansyah; Helmi Imaduddin (Rang Teknik Journal, 2026)
In the contemporary age of digital transformation, where the necessity for efficiency and precision is critical, numerous firms encounter substantial challenges in properly managing their inventory systems, particularly in the context of rising product demand and operational intricacy. PT. Perdana Sakti Indonesia faces significant challenges due to its reliance on manual data processing methods, resulting in data entry errors, delays in stock information updates, and protracted calculation processes that impede productivity and responsiveness. The deficiencies in inventory management jeopardize financial stability and reduce consumer happiness, particularly when products are out of stock or delivery schedules are disrupted. This project seeks to design and create a complete web-based inventory information system utilizing the Waterfall methodology as a systematic software development framework. The system is built with Laravel as the primary framework, PHP for backend development, MySQL as the database engine, and HTML/CSS for designing a user-friendly interface. The use of automation and real-time monitoring is anticipated to markedly boost data accuracy, minimize human errors, optimize stock management, and improve overall operational efficiency. The use of this system is anticipated to enhance PT. Perdana Sakti Indonesia's inventory management and service quality.